ESTUDO DOS EFEITOS DA ADIÇÃO DE V₂O₅ EM PROPRIEDADES FÍSICOQUÍMICAS E BIOATIVAS DE VIDROS DO SISTEMA B₂O₃-P₂O₅-SrO-K₂O - RODRIGUES, Francisco Wallis Sousa (2025)
Bioactive borophosphate glasses have gained increasing attention due to their ability to dissolve while maintaining a neutral pH, release therapeutic ions, and exhibit biodegradable properties. The addition of V₂O₅ to bioactive glasses has demonstrated biocompatibility and osteogenic potential, potentially accelerating bone regeneration. This study aimed to investigate the effect of vanadium pentoxide addition on borophosphate glasses in the system 50B₂O₃-(20-x)P₂O₅-20SrO-10K₂O-xV₂O₅ (x = 0; 0.25; 0.5; 1; 1.5; and 2 mol%), evaluating the physicochemical properties and biocompatibility of the samples. For substitutions of P₂O₅ with V₂O₅ up to 1 mol%, in vitro bioactivity and antibacterial activity were also assessed. The samples were synthesized using the melt-quenching method. The physicochemical properties were characterized by XRD, density, Raman, FTIR, optical absorption spectroscopy, DSC analysis, N₄ calculation, molar volume (Vm), and molecular dynamics (MD). In vitro tests evaluated the biocompatibility, antibacterial effect, and bioactivity of the samples, with bioactivity assessed after immersion in SBF for 3, 7, 14, 21, and 28 days. Optical absorption spectroscopy confirmed changes in V⁵⁺/V⁴⁺ coordination and a reduction in the band gap. The substitution with V₂O₅ increased bands associated with BO₄ and decreased those related to BO₃ in FTIR spectra, consistent with N₄ values. A reduction in the glass transition temperature (Tg) and an increase in glass radiopacity were observed with increasing V₂O₅ content. In the cytotoxicity test, the samples with up to 1 mol% of V₂O₅ (BPSrK-V1) showed no cytotoxicity, and therefore, bioactivity assays were performed for these samples. XRD confirmed the amorphous nature of the samples before immersion and the formation of hydroxyapatite (HA) and amorphous calcium phosphate in SBF-immersed samples, while FTIR confirmed the vibrational modes corresponding to these phases. All glass samples exhibited antibacterial activity against both Grampositive and Gram-negative bacteria. MD simulations explored structural characteristics such as coordination number, pair distribution function, and bond angle distribution, showing good agreement with experimental results, including N4. These findings suggest that up to 1 mol% V₂O₅ substitution in the borophosphate matrix renders these materials promising candidates for biomedical applications.